1988
DOI: 10.1111/j.1399-3054.1988.tb09176.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the activity and capacity of the alternative pathway in intact plant tissues: Identification of problems and possible solutions

Abstract: Møller, I. M., Bérczi, A., van der Plas, L. H. W. and Lambers, H. 1988. Measurement of the activity and capacity of the alternative pathway in intact plant tissues: Identification of problems and possible solutions. ‐ Physiol. Plant. 72: 642–649. The cyanide‐insensitive, benzhydroxamic acid‐sensitive (e.g. salicylhydroxamic acid, SHAM) alternative pathway is located in the inner membrane of plant mitochondria and electron flow through it is not coupled to H+ pumping and ATP synthesis. When estimating the activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
98
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(101 citation statements)
references
References 27 publications
3
98
0
Order By: Relevance
“…Results such as these have been reported earlier (3,22,24) The respiratory analysis of male-fertile and male-sterile Nicotiana materials revealed a great difference in the capacity of the alternative pathway between mitochondria isolated from green leaves and cells in suspension culture. However, no obvious correlation between respiratory characteristics and CMS was detected in either type of material.…”
Section: Discussionsupporting
confidence: 53%
“…Results such as these have been reported earlier (3,22,24) The respiratory analysis of male-fertile and male-sterile Nicotiana materials revealed a great difference in the capacity of the alternative pathway between mitochondria isolated from green leaves and cells in suspension culture. However, no obvious correlation between respiratory characteristics and CMS was detected in either type of material.…”
Section: Discussionsupporting
confidence: 53%
“…The results of a previous report indicated that estimates of the alternative pathway in intact tissues and in mitochondria both indicate higher levels in cold-grown shoots (7). Corn shoot tissues appear to satisfy the conditions set down by Moller et al (15) for using intact tissue measurements for estimating the alternative pathway. Thus, both intact corn tissues and mitochondria isolated from them can be used to measure alternative oxidase capacities.…”
mentioning
confidence: 56%
“…The role of this activity as a thermogenic process during reproductive development has been established as well as its induction by salicylic acid (16). During the current decade, attention has been directed to understanding the occurrence and function of the alternative oxidase in a wide variety of plant species and tissues, including crop species ( 15).…”
mentioning
confidence: 99%
“…1C). Between 12 and 48 h, respiration rate grad- (18), but note that these terms are somewhat redefined here in that they may be measured in the presence of AA. All of the above data were calculated from the results presented in Figure 1.…”
Section: Respiratory Characteristics and Growthmentioning
confidence: 99%